Theoretical Study of The Structure of Anthocyanin Dyes to Improve The Performance of Dye Sensitized Solar Cells (DSSCs) - Imelda; Jusmarni; Aziz, Hermansyah; Deswita, Elvira; Admi; Ostari, Dwi Ningsih (Hydrogen: Jurnal Kependidikan Kimia, 2026)
In this study, anthocyanin dyes have been designed in two ways: without modification and with modification, incorporating donor chains and π-chains, and forming the structure of type D-π-A dyes. The anthocyanin dyes used are delphinidine, cyanidin, pelargonidin, malvidin, petunidine, and fragarine. Meanwhile, the modified molecule is a combination of anthocyanin dye as an acceptor chain, coumarin as a donor chain, and 1,4-dihydro-pyrrolo[3,2-b]pyrrole as a π-conjugation chain. The molecular structure was calculated using a 16W Gaussian Software with the DFT method and the B3LYP/6-31G base set. The results of the calculation on the dye without modification showed that the malvidin dye produced the smallest bandgap of 2.4085 eV and the largest light absorption. Meanwhile, the results of the calculation of the modified dye showed that the modified dye with the delphinidin acceptor produced the smallest bandgap of 1.4485 eV and the largest light absorption. In conclusion, modified anthocyanin dyes can improve the light absorption efficiency in DSSCs.